Visiting Ladakh Himalaya for a better knowledge of butterflies: new faunistic data with annotations (Lepidoptera, Papilionoidea) - Das, Gaurab Nandi; Ali, Mohd; Bálint, Zsolt; Singh, Navneet; Chandra, Kailash; Gupta, Sandeep Kumar (Zootaxa, 2023)
The present study enumerates 65 species of Papilionoidea from the Ladakh Himalaya with the geographical locations and adult flight data. All the species are documented by museum vouchers. Most of the species recorded, have restricted distribution or they are endemic to the Pamir–NW Himalaya region. Sixteen species are protected in the Indian Wildlife (Protection) Act, 1972; three species highly protected under schedule I: Baltia butleri, Pieris krueperi, Lasiommata menava; and others under schedule II: Papilio machaon, Parnassius charltonius, Parnassius epaphus, Colias ladakensis, Colias eogene, Colias stoliczkana, Pieris deota, Pontia chloridice, Alpherakya devanica, Pamiria metallica, Paralasa mani, Paralasa kalinda and Polygonia c-album. We report lower occurrences for the endemic Pieris deota, where the migrant Pontia chloridice is reported to fly at more than 600 m higher than earlier records indicated. Lastly, the male and female genitalia of some endemic and rare species are illustrated, including Euchloe daphalis.